P5.090 Evaluation of a Double Rapid Test For Syphilis and HIV: SD Bioline HIV/Syphilis Duo. (13th July 2013) - Chiappe, M A; Lopez-Torres, L; Carcamo, C; Garcia, P; Peeling, R
Abstract : Background: Although syphilis and HIV are primarily transmitted through sexual intercourse, they can also be transmitted from mother to child during pregnancy or at delivery. Testing pregnant women for syphilis and HIV is an important public health measure to prevent vertical transmission. Several countries have included screening of pregnant women using rapid HIV testing, and recently also rapid syphilis testing. Screening pregnant women for both diseases with one test is not only desirable but could also be very convenient. We present the results of the laboratory-based evaluation of a new test: the SD Bioline HIV/Syphilis Duo. Methods: We used archived serum specimens characterised as positive or negative for HIV and/or Syphilis. The gold standard positive for HIV was EIA (Vironostika ® HIV Uni-Form II Ag/Ab, bioMérieux) with confirmation using Western blot. The reference standard positive for syphilis was the Rapid Plasma Reagin test (RPR, bioMérieux) with confirmation using the Treponema pallidum Particle Agglutination (TPPA) assay (Fujireibio, Japan). Reference standard negatives were EIA negative and RPR negative for HIV and syphilis respectively. For Syphilis we used a total of 665 samples, including 198 positives, and for HIV we used 662 samples including 91 positives. There were 42 samples positive for both HIV and syphilis. The samples were tested with the SD Bioline HIV/Syphilis Duo by a laboratory technician blinded to the gold standard results. Results: For Syphilis we observed a sensitivity of 100% (198/198) and a specificity of 99.57% (465/467). The two RPR negative/Bioline positive samples were negative for TPPA. For HIV, both the sensitivity and specificity were 100% (91/91 and 571/571 respectively). Conclusions: The SD Bioline HIV/Syphilis Duo test has a good performance in archived sera. Its high sensitivity suggests that this dual test would be of use in screening programmes for syphilis and HIV.